The Removal Method of the Blasting Vibration Signal Trend Item and Noise - Hailong Wang; Haobo Bai; Yan Zhao; Dongsheng Wang; Xiaojing Wang; Shenghua Wang (Shock and Vibration)
Aiming at the problem that the blasting vibration signal contains trend items and noise interference, a signal processing method based on the Fourier decomposition method (FDM) is introduced. Firstly, based on the FDM theory, the original blasting vibration signal is decomposed to obtain several modal components; then, the dominant component of the signal is filtered according to the dominant frequency of the modal component and its correlation with the original signal; finally, the dominant component is reconstructed to remove the trend item and noise at the same time; spectrum analysis is carried out to verify the effectiveness of the method. The results show that FDM can effectively disperse low-frequency trend items, high-frequency noise, and useful signal information while decomposing signals containing trend terms and noise; compared with the existing common methods, it can more effectively retain the original information, which provides a reference for the trend item and noise removal of similar blasting vibration signals.